The Effect of Knowledge Sharing and Self Efficacy on the Performance of KPPBC TMP B Yogyakarta Employees with Organizational Commitment as a Mediation Variable - Triana Candraningrum; Rini Dwiyani Hadiwidjaja; Yanuar Trisnowati (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the effect of knowledge sharing and self efficacy on employee performance through organizational commitment at KPPBC TMP B Yogyakarta. The study was motivated by the decline in service quality reflected in the User Satisfaction Survey (SKPJ), particularly in service speed and officers’ mastery of service materials. This research used a quantitative approach with an explanatory research design. The population consisted of all 135 employees of KPPBC TMP B Yogyakarta. The sampling technique used was a census or saturated sampling method, in which all population members were selected as respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling – Partial Least Square (SEM-PLS) with SmartPLS version 4. The results showed that knowledge sharing had a positive and significant effect on organizational commitment and employee performance. Self efficacy also had a positive and significant effect on organizational commitment and employee performance. In addition, organizational commitment had a positive and significant effect on employee performance. Furthermore, organizational commitment was proven to mediate the effect of knowledge sharing and self efficacy on employee performance. The managerial implication of this study indicates that organizations need to strengthen the culture of knowledge sharing and improve employees’ self efficacy through mentoring, training, and work experience sharing forums to support employee performance improvement.